(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In this article, the family is an integral part of society, the role of the family in the upbringing of harmoniously developed people, the family life of the Uzbek people in the works of ancestors, the national characteristics of the relationship, the duties and responsibilities of the couple, family lifestyle, educational environment and its importance in society. the role of parents, pedagogical and psychological information on family upbringing in the legacy of Eastern thinkers.